1973
DOI: 10.3758/bf03207231
|View full text |Cite
|
Sign up to set email alerts
|

Figural goodness and the predictability of figural elements

Abstract: All 1:6 patterns composed of five dots distributed over the cells of a 3 by 3 matrix were examined for the predictability of their elements. The predictability of a given dot in a given pattern was measured as the percentage of Ss who indicated that dot as one "implied or suggested" by the subpattern composed of the remaining four dots of the pattern. The dots comprising a figurally good five-dot pattern were generally more predictable. one from the others. than the dots comprising a poor pattern. This finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

1974
1974
2000
2000

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 13 publications
1
9
0
Order By: Relevance
“…Yet research on pattern goodness suggests that grouping is not simply present or absent. These studies (e.g., Bear, 1973;Bell & Handel, 1976) have shown that global patterns can differ in the degree to which they organize and in how well they can specify the relative location of local units. Global patterns that are simple or redundant in structure are processed more quickly and accurately than others in information-processing tasks (e.g., Gamer & Sutliff, 1974;Sebrechts & Gamer, 1981).…”
Section: Purpose Of the Present Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Yet research on pattern goodness suggests that grouping is not simply present or absent. These studies (e.g., Bear, 1973;Bell & Handel, 1976) have shown that global patterns can differ in the degree to which they organize and in how well they can specify the relative location of local units. Global patterns that are simple or redundant in structure are processed more quickly and accurately than others in information-processing tasks (e.g., Gamer & Sutliff, 1974;Sebrechts & Gamer, 1981).…”
Section: Purpose Of the Present Studymentioning
confidence: 99%
“…Several of these studies (e.g., Attneave, 1955;Bear, 1973;Schnore & Partington, 1967) have shown that the location of the local units can be remembered or predicted better with stimuli that are structurally redundant (i.e., good patterns) than with stimuli that are not (i.e., poor patterns). All of these studies have used stimuli such as dot patterns that differ only globally in the relative location of the local units (i.e., not in the number of absolute locations).…”
mentioning
confidence: 99%
“…For example, when a task requires encoding a stimulus into a form suitable for storage in and retrieval from memory, a more detailed analysis of stimulus structure may take place. Good patterns are redundant (Bear, 1973;Garner, 1970), and so can be specified with a smaller number of features than can poor patterns. This allows good patterns to be encoded into memory in a shorter time.…”
Section: When Does Goodness Affect Encoding?mentioning
confidence: 99%
“…They were obtained by the present author (Bear, 1973) from Ss who were shown a11 possible four-dot subpatterns and asked to add to each a fifth dot "implied or suggested by those already present." The percentage of Ss who placed their dot in a given position in response to a given configuration of four dots was taken as an index of the predictability of that dot in the total five-dot pattern.…”
Section: Predictabilities Of the Dotsmentioning
confidence: 99%